Impact of advertisement and price on consumer purchase decision - Manandhar, Binita (Management Dynamics, 2020)
Advertisement and price play crucial role in consumer buying behavior. The purpose of this study is to measure the impact of advertisement and price in consumer buying behavior. The data were collected by questionnaires using convenient sampling, a sample 400 questionnaire were distributed and 370 complete questionnaires were received from the respondents. Data were analyzed by using different statistical technique such as descriptive static, correlation analysis and regression analysis. The findings of the study showed that advertisement and price have significant impact on consumer purchase decision. Gender and academic qualification were also included as moderating variables and found no significant influence of such variables on consumer purchase decision.